High-resolution EPR distance measurements on RNA and DNA with the non-covalent Ǵ spin label. Issue 2 (28th November 2019) - Heinz, Marcel; Erlenbach, Nicole; Stelzl, Lukas S; Thierolf, Grace; Kamble, Nilesh R; Sigurdsson, Snorri Th; Prisner, Thomas F; Hummer, Gerhard
Abstract: Pulsed electron paramagnetic resonance (EPR) experiments, among them most prominently pulsed electron-electron double resonance experiments (PELDOR/DEER), resolve the conformational dynamics of nucleic acids with high resolution. The wide application of these powerful experiments is limited by the synthetic complexity of some of the best-performing spin labels. The recently developed G (G-spin) label, an isoindoline-nitroxide derivative of guanine, can be incorporated non-covalently into DNA and RNA duplexes via Watson-Crick base pairing in an abasic site. We used PELDOR and molecular dynamics (MD) simulations to characterize G, obtaining excellent agreement between experiments and time traces calculated from MD simulations of RNA and DNA double helices with explicitly modeled G bound in two abasic sites. The MD simulations reveal stable hydrogen bonds between the spin labels and the paired cytosines. The abasic sites do not significantly perturb the helical structure. G remains rigidly bound to helical RNA and DNA. The distance distributions between the two bound G labels are not substantially broadened by spin-label motions in the abasic site and agree well between experiment and MD. G and similar non-covalently attached spin labels promise high-quality distance and orientation information, also of complexes of nucleic acids and proteins.